Development of a Penetration Testing Framework for Identifying Security Vulnerability Solutions in WiFi Networks: Pengembangan Framewok Penetration Testing untuk Proses Pencarian Solusi Kerentanan Keamanan pada Jaringan Wifi - Imran, Ali; Neyman, Shelvie Nidya; Rahmawan, Hendra (Telematika, 2025)
The rapid increase in internet users has driven the development of WiFi networks, which play a crucial role in providing secure internet access, especially within Industry 4.0 and Industry 5.0 environments that rely on efficient data exchange. Penetration testing (pentest) is a vital approach for auditing and evaluating the security level of WiFi networks. Several frameworks such as PTES, PETA, and ISSAF are often used as references, although only a few are explicitly designed for WiFi networks. This study proposes a modification of the PTES framework to better align with the security characteristics of WiFi networks by providing relevant solution recommendations. The integration of the Boyer-Moore algorithm is employed as an efficient method to identify solutions for detected vulnerabilities. The implementation of this framework is demonstrated through testing the suggestion process, which produces solution recommendations based on vulnerabilities found during the pentest. The Boyer-Moore algorithm exhibits high efficiency in generating recommendations with a response time of 0.0000087 seconds.